The potential mechanisms of tissue flossing with Flossband application around the joints or soft tissues: A theoretical framework - Jianhong Gao; Jin Seng Thung; Chen Soon Chee; Chris Chow Li Tee; Tengku Fadilah Tengku Kamalden; Shamsulariffin Samsudin; Azril Syazwan Bin Mohd Ali (Apunts Sports Medicine)
Flossband application in rehabilitation and sports medicine has been demonstrated to increase flexibility, improve muscle strength, dampen pain, and reduce inflammation. However, scarce evidence has presented the latent mechanisms that explain the beneficial effects of Flossband application. To fill the knowledge gap about the Flossband wrapping mechanisms and Flossband application mastering, an initial theoretical framework delineating the advantages of Flossband application mechanisms is needed. Therefore, based on the current evidence, this paper aims to summarize the potential mechanisms of the Flossband application benefits. The primary speculated mechanisms, “Pain Gate”, “Fascia Glide”, “Sponge Effect”, “Soft Tissue Ischemia”, and “Joint Effect” were proposed to illustrate how Flossband application works on soft tissues or joints to reduce pain, release fascia tension, improve muscle flexibility, decrease inflammation, and enhance muscle activation. The benefits derived from the Flossband application may be more effectively elucidated through the interaction of the five primary mechanisms mentioned above, whether applied to soft tissues or joints rather than relying on a singular mechanism. This consideration acknowledges the complexity and interactivity inherent in the Flossband application.